Pengaruh Penerapan E-Procurement dan Kompetensi Pegawai Terhadap Pencegahan Kecurangan Pengadaan Barang dan Jasa - Affillah Syayyid Kholby; Vina Citra Mulyandani; Rendra Trisyanto Surya (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Abstract: Procurement of government goods and services in the traditional way is known to have many loopholes for unscrupulous persons to commit fraud. To overcome this, the government innovates the e-procurement system. The E-procurement system cannot stand alone in preventing fraud, there must be other components such as human beings who have competence in conducting procurement. Although innovations have been made, fraud in goods and services is still common in the government, especially in South Tangerang City. This quantitative research using multiple linear regression was conducted to determine how much influence e-procurement and human resource competence have on the prevention of fraud in government goods and services in South Tangerang City. The results of this study indicate that the application of e-procurement and employee competence has a positive effect partially, and simultaneously has an effect on preventing fraud in goods and services.